The Transformation of Iddah Law: Towards Gender Equality and Family Justice in Islamic Society - Maya Aufa; Nurul Ma’rifah; Ma’zumi (LP2M IAIN Palopo, 2026)
This research is intended to offer a strategy for reforming iddah law in improving women's empowerment and family justice. Qualitative research, with the Library Research approach, this study investigates the concept of iddah law, its implementation in society, as well as the obstacles that may be faced, and strategies that can be offered for the renewal of iddah law with a focus on achieving gender equality and family justice. The results of the study show that iddah law has a central role in the structure of Islamic family law, but its implementation can pose challenges related to gender equality. These obstacles include aspects of conservative interpretation, social norms, and resistance to change. The strategy offered is the collaborative involvement of religious institutions, the government through a community education approach to create a more inclusive legal environment and support women's empowerment and family justice. It is hoped that the implementation of this strategy can have a positive impact on changes in social norms, reduce gender inequality, and create a basis for a more equitable family life in the context of Islamic society.